A BOOK REVIEW: THEORY AND PRACTICE OF ENGLISH LANGUAGE TEACHING IN INDONESIAN CONTEXT - Shirly Rizki Kusumanigrum (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
Few days before I had my thesis examination, I met my Professor. He offered me to type some manuscripts to be published in a book. With pleasure, I accepted his offer. By the time I read the manuscripts, I got lots of information about English Language Teaching in Indonesia. Finally, the time comes; and the manuscripts are compiled into a book entitled "The Teaching of English as a Foreign Language in Indonesia." This book is actually a compilation of manuscripts written by Bambang Yudi Cahyono and Utami Widiati, two professors at English Department of State University of Malang. There are 9 chapters in this book in which the content is about English Language Teaching in the Indonesian context. Therefore, in this review, I will discuss the contents of the book, as well as highlight the benefits of this book related to English Language Teaching in Indonesia.